Evaluation of Photocatalytic and Catalytic Activity of Biochar/Nickel for Laboratory Wastewater Treatment - Fatimah, Is; Solekah; Nurlaela, Nunung; Ahmad, Zeeshan; Rizky, Indah Tri; Kamari, Azlan; Sagadevan, Suresh; Doong, Ruey-an (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
In this investigation, an exploration on the use of low-cost effective methods for laboratory wastewater treatment using magnetic biochar has been conducted. Magnetic biochar derived from orange peel waste loaded with nickel nanoparticles (Biochar/Ni) was prepared by pyrolysis procedure of orange peel waste with nickel chloride as nickel precursor at 600 oC for 2 h. X-ray diffraction (XRD), scanning electron microscopy-energy dispersive x-ray (SEM-EDX), Raman spectroscopy, and vibrating sample magnetometer (VSM) were employed for identify the feature of Biochar/Ni. Photocatalytic, photocatalytic oxidation, and microwave-assisted catalytic peroxidation were the treatment procedures employed to evaluate the activity of Biochar/Ni. The results showed the dispersed nickel nanoparticles in the composite are photocatalytic system to produce radicals for decolorizing laboratory wastewater as proven by accelerated oxidation by the addition of H2O2 and S2O82- as oxidants, and inhibition by the addition of radicals and superoxide radical scavengers. In addition, microwave-irradiation intensified catalytic peroxidation with shorter time and higher decolorization efficiency. The greenness evaluation of the process using AGREE software addressed the microwave-assisted catalytic peroxidation as the most efficient procedure utilizing Biochar/Ni for being developed and implemented to organic contaminated wastewater.